تغيرات درجة الحرارة في محطتي طرطوس وصافيتا خلال الفترة 2010-1960 - سكاف, ميشيل; رنجوس, ليال (Latakia University Journal -Biological Sciences Series, 2018)
Climate change is considered as one of the most important challenges facing society and environment during the last decades in several parts of the world. seasonal and annual average of maximum and minimum temperatures for Safita and Tartous during the period 1960-2010 were used to detect changes in temperature regime in some parts of syrian coastal region,. Z-Score was calculated for Tmax and Tmin according to the mean of the standard period 1960-1990. Moving average and point change analyzes were used to detect changes in seasonal and annual temperature time serieses. Normal distribution was computed for two periods 1960-1985 and 1986-2010 to detect changes in probability of high temperatures. Results showed significant shift in annual temperatures during last two decades due to increasing tendency in maximum and minimum temperatures for warm period, especially in summer and spring. We also found that probability of extreme high temperature increased during the second half of the study period. This changes in temperature will pose threat to the agricultural production and natural ecosystem in this region. يعد تغير المناخ من أهم التحديات التي تواجه المجتمعات البشرية والنظم البيئية خلال العقود الأخيرة في مختلف مناطق العالم. استخدمت متوسطات الحرارة الفصلية والسنوية لدرجات الحرارة العظمى والصغرى للفترة 2010-1960 لكل من صافيتا وطرطوس للتحقق من التغير في النظام الحراري في بعض أجزاء المنطقة الساحلية من سوريا. تم حساب الانحرافات القياسية لكل من الحرارة العظمى والصغرى بالنسبة لمعدل الفترة 1990-1960 كما استخدم المتوسط المتحرك واختبار نقطة التغير للتحقق من حدوث التغير في السلاسل الفصلية والسنوية لدرجات الحرارة. تم تطبيق التوزع الطبيعي على كلا الفترتين 1985-1960 و 2010-1986 لدراسة التغير في احتمالية حدوث درجات الحرارة المرتفعة. أظهرت النتائج انزياحاً واضحاً ومعنوياً في معدلات الحرارة السنوية خلال العقدين الأخيرين بسبب الاتجاه نحو الزيادة في درجات الحرارة العظمى والصغرى خلال الفترة الدافئة من العام وخاصة في الصيف والربيع، كذلك بينت النتائج أن احتمال حدوث حرارة متطرفة تزايد خلال الفترة الثانية من الدراسة بشكل ملحوظ. إن هذه التغيرات في الحرارة ستشكل تهديداً للإنتاج الزراعي والنظم البيئية الطبيعية في هذه المنطقة.